Pharmacokinetics and pharmacodynamics of vincristine sulfate liposome injection (VSLI) in adults with acute lymphoblastic leukemia. (17th August 2013) - Silverman, Jeffrey A.; Reynolds, Laurie; Deitcher, Steven R.
Abstract Vincristine sulfate liposome injection (VSLI, ) is a sphingomyelin and cholesterol nanoparticle formulation of vincristine sulfate (VCR) that was designed to overcome the dosing and pharmacokinetic limitations of standard VCR. In contrast to the rapid CL and wide tissue distribution of non‐liposomal VCR, VSLI circulates in plasma for a prolonged period of time, with a slow CL of 345 mL/h and relatively small Vd of 3, 570 mL. This facilitates enhanced and prolonged tumor‐tissue delivery of VCR. The maximum tolerated dose of VSLI, 2.25 mg/m2 once per week without a dose cap, enables individual and cumulative VCR exposure unachievable with non‐liposomal VCR at its labeled dose of 1.4 mg/m2. VSLI is associated with a dose‐dependent peripheral neurotoxicity albeit at doses that are two to three times that of standard VCR. VCR dose intensification with VSLI correlated with an increased probability of overall response and a strong trend towards increased complete response in adults with relapsed and/or refractory acute lymphoblastic leukemia. Overall, VSLI improves the therapeutic index by facilitating increased dose intensification while maintaining a predictable and manageable safety profile.